Socioeconomic and Demographic Disparities in Symptoms of Orofacial Pain - Joseph L. Riley, 111, PhD; Gregg H. Gilbert, DDS, MBA; Marc W. Heft, DMD, PhD (Blackwell Synergy, 2003)
The purpose of this study was to document the association between socioeconomic status (SES) and the prevalence and impact of orofacial pain by anatomical location. In addition, differential effects of SES on orofacial pain across levels of sex, race, and age were documented